Desenvolvimento de uma proposta para o controle executivo de estacas do tipo de raiz - Monteiro, Fernando Feitosa (2016)
The foundations project is started from the planning of adequate geotechnical investigation, later, with the choice of the most suitable foundation solution for the work. The performance of foundations is verified from the executive control. For root-type piles, control is usually performed based on static load tests. To study the performance of root cuttings, static load tests are performed on 8 monitored stakes with diameters of 350 and 410 mm. This paper aims to develop an empirical formulation for the prediction of the load capacity of root cuttings based on the proposals initiated by Lima (2014) and Moura et al. (2015). The sites of the works were previously selected and present substrates with variable stratigraphy. These same stakes were monitored by means of variables obtained during the monitoring that were related to the parcels of the load capacity of tip and lateral. Afterwards, an expression was used to predict the load capacity of the stakes tested, according to the variables monitored, using the value obtained according to the Van der Veen method (1953) and using multiple linear regression. It was verified that there is a correlation between the load capacity and the monitored variables. Thus, different scenarios were proposed, where in one of them the lateral load capacity of the stakes is responsible for 80% of the total load capacity and the load capacity of the load that accounts for 20% of the total load capacity. In the other scenarios, simulations were developed in which the side of the stakes would withstand 90% of the load capacity and the tip 10%, and finally, it was considered the situation that the load capacity is totally absorbed by the side of the stake. The results obtained by the proposed expressions were in agreement with the reference values ​​for the stakes tested. The Lizzi method (1982) presented estimates more in agreement with the results obtained in the proposed formulation that correlates load capacity and the variables monitored in the executive process. From the realization of this research, it is observed that the proposed methodology presents itself as a viable alternative for the executive control of root cuttings.